Pengaruh Likuiditas terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening dan Kepemilikan Manajerial sebagai Variabel Moderasi: (Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2014 – 2023) - Nurul Yasmin Fauziah; Fauji Sanusi; Ana Susi Mulyani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study analyzes how profitability and managerial ownership moderate the effect of liquidity on firm value. Property and real estate companies listed on the Indonesia Stock Exchange (IDX) were studied from 2014 to 2023. Non-probability and purposive sampling were used for quantitative analysis. Seven out of 48 companies were selected based on criteria. The analysis was conducted with Eviews 12. This study found that (1) liquidity has a negative and significant effect on firm value, (2) liquidity has no and insignificant effect on profitability, (3) profitability has a positive and significant effect on firm value, (4) profitability cannot mediate the relationship, and (5) managerial ownership moderates the relationship.